2017
DOI: 10.1093/dote/dox046
|View full text |Cite
|
Sign up to set email alerts
|

Validation of EORTC QLQ-OES18 for Chinese patients with esophageal cancer

Abstract: The aim of this study is to evaluate the reliability, validity, and acceptability of the Chinese version of the EORTC QLQ-OES18 in patients with esophageal cancer. The questionnaire was translated according to the guideline of the EORTC. One hundred and forty-nine patients with esophageal cancer from Tianjin Medical University Cancer Institute and Hospital completed the Karnofsky performance scale (KPS) and the simplified Chinese EORTC QLQ-C30/OES18 scales during July 2013 to January 2014. The results were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…It consists of four symptom subscales (dysphagia, difficulty with eating, reflux, and pain) and six single items (trouble swallowing saliva, choking at swallowing, dry mouth, trouble with tasting, coughing, and talking). The Chinese version of the scale is reliable and acceptable to measure the health-related QOL of patients with esophageal cancer in China [ 41 ]. In addition to QOL, the patients’ body weight and physical fitness measured by the 6MWD were assessed by medical doctors.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of four symptom subscales (dysphagia, difficulty with eating, reflux, and pain) and six single items (trouble swallowing saliva, choking at swallowing, dry mouth, trouble with tasting, coughing, and talking). The Chinese version of the scale is reliable and acceptable to measure the health-related QOL of patients with esophageal cancer in China [ 41 ]. In addition to QOL, the patients’ body weight and physical fitness measured by the 6MWD were assessed by medical doctors.…”
Section: Methodsmentioning
confidence: 99%
“…VMAT was commonly used in our study. Clinical research and methodological studies relating to the treatment of esophageal cancer have shown that IMRT or VMAT are better than 3DCRT with respect to improved target coverage and conformality, in addition to reduced radiation exposure to adjacent organs [25, 26]. This may be the reason why our results were favorable.…”
Section: Discussionmentioning
confidence: 82%
“…The OES18 is a supplementary symptom scale for esophageal cancer, which specifically includes 18 items such as dysphagia, eating, reflux, pain, saliva, choking, dry mouth, loss of appetite, cough, and speech (12). Many clinical trials, including trials conducted in a Chinese population, have proven that the combined application of QLQ-C30 and QLQ-OES18 can more accurately reflect the relationship between the symptoms of esophageal cancer patients and their QOL (22,23).…”
Section: Discussionmentioning
confidence: 99%